INTERVENSI PENERAPAN TEORI BELAJAR BEHAVIORISME DALAM PROSES PEMBELAJARAN DI TINGKAT SEKOLAH DASAR - Sabiily, M. Arsyada; Ratnaningrum, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article focuses on research which aims to investigate the intervention of behaviorist learning theory in the learning process at the elementary school level for students in class IV at SDN Beringin 02. The aim of this research is to find out; (1) how the disciplinary character of students has been formed so far in class IV SDN Beringin 02, (2) what is the behavior and characteristics of students in learning, (3) what is the role of students and teachers/educators in behaviorist learning theory, (4) how the role of students and teachers/educators in behaviorist learning theory, (4) how to intervene in the application of behaviorist learning theory in learning in class IV with aspects of the disciplined character of students raised in it. This research will help understand the importance of teacher intervention in improving student learning based on behaviorist learning theory. Using a qualitative descriptive approach including interviews, observation and documentation, this research was conducted during break times, namely 10:00 AM - 11:00 AM at SDN Beringin 02. This program succeeded in improving teachers' abilities in implementing interventions to apply behaviorist learning theory in learning. The intervention process begins with identifying types of learning styles, identifying types/factors of student learning behavior, planning (preparing programs, preparing instruments), implementing (direct intervention, through media, through methods, peer tutoring, parent involvement, remedial, and enrichment). ), as well as evaluation and follow-up.